Sinergitas Mahasiswa KKN 352-Sisdamas dan Masyarakat Desa Pusakajaya Dalam Sertifikasi Usaha Mikro Kecil dan Menengah (UMKM) - Nurliana, Diana; Nanta Setia; Rahul Achmad Fadillah; Syifa Fadia; Asep Shodiqin (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Field Workl Lecture (KKN) is a tangible manifestation of lesturers and students duties in implementing the Tri Darma of Higher Education, namely the aspect of dedication. Through community sevice activities in Pusakajaya village. There will be synergy between universities and the community as a form of democratic knowledge. KKN Sisdamas is a Real Work Lecture which is carried out offline at a predetermined location based on community empowerment. The implementation of the KKN Sisdamas Regular is packaged by combining the social learning process for KKN participants, community service, and social research through the stages of the empowerment cycle. The service is carried out through activities: Gathering with Pusakajaya residents, Socialization of the Environment, Socialization of the impact of gadgets, KKN Teaching, Smart home program, Mutual cooperation in cleanliness. The results of the service illustrate the increasing enthusiasm and initiative of the village community regarding the importance of protecting the environment and managing waste, the importance of being wise in giving gadgets to children, and the increasing level of public awareness about the importance of education as an investment in the future, study assistance and making intangible tools for villages as materials to facilitate the work of village officials in their duties.